Environmental Print Model Based on Family Stimulation Solutions Ability Reading Initial Children in the Era of Pandemic Virus Dangerous - Ismaniar, Ismaniar (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2020)
The turbulence of Coronaviruses sometime this past raises fear and anxiety for everyone. Moreover, the spread of this virus has penetrated all over the country so it is expressed as a pandemic condition. One of the solutions highly recommended by the WHO and supported by health experts and government policy is to keep social distance physically. These conditions include the impact on the application of the program at home only. In the educational world, social distancing policies also impact child education, which leads to the role of education in returning to the family. For the stimulation of children's education is not stopped, parents need to use creative models to stimulate children's abilities. One model that can be used in stimulating the ability of children, especially the ability to read early children is to use a family-based environmental Print model. This model is one of the simulation models by engineered the environment around the house by expanding the patch of the writings by observing the children's favorite places and favorites.Keywords: Environmental Print, Family, Solutions, Stimulation, Early Reading, Pandemic Era